Political Economy Risks of Indonesia’s New Capital City Development - Maria Chrismastyani Pratiwi; Suzanna Ratih Sari (Jurnal Riset Multidisiplin Edukasi, 2026)
The choice made by Indonesia to shift its seat of government to IKN Nusantara stands out as one of the most far-reaching, state-driven urban ventures anywhere in Southeast Asia, carrying political and economic implications that extend well beyond the immediate project. Although officials present the initiative as a solution to Jakarta’s congestion, ecological strain, and administrative shortcomings, whether it can remain economically viable over the long run is still an open question. Adopting a political economy lens, this research looks closely at the project’s institutional makeup, its exposure to fiscal risk, and the time-horizon hazards typically associated with purpose-built capitals. Combining comparative indicator analysis of several planned capitals with an assessment of fiscal and temporal risk, the research follows a mixed qualitative–quantitative design. Descriptive indicators are applied to gauge population size, the breadth of economic diversification, dependence on transport, and the timeframe for implementation. Results show that IKN Nusantara mirrors structural traits found in earlier planned capitals—namely, a dominant administrative role, substantial dependence on state funding, and extended construction periods that raise the likelihood of cost overruns and institutional inflexibility. Absent solid mechanisms for diversifying the economy and adapting governance practices, the study contends that IKN Nusantara may end up as a fiscal burden that remains dependent on government spending, ultimately constraining its capacity to support broader national development goals.